The Effect of Wages, Economic Growth, and Number of Industries on Unemployment - Mulya Pratomo , Ade; Setyadharma, Andryan (KnE Social Sciences, 2020)
The purpose of this study was to determine the effect of minimum wages, economic growth, and number of industries on unemployment in West Java Province. In this study, the number of industries variable also acts as a moderator variable. The method of data analysis in this study is data panel regression. The data used is from secondary data obtained from Badan Pusat Statistik (BPS) in 2013-2015 with 26 districts and cities in West Java Province. The results showed that the minimum wage and the number of industries have positive and significant effects on unemployment, while economic growth has not significant effect on unemployment. The interaction between moderating variable and the minimum wages and economic growth variables have negative and significant effects on the unemployment. The interaction between the moderating variable and two other variables strengthens the influence of independent variables on the dependent variable.